Inclusive Leadership Strategy in Islamic Educational Institutions to Build Harmony and Collaboration at MTS Negeri 2 Karawang - Arya Budiman; Sayan Suryana; Khalid Ramdhani (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the implementation of multicultural management in Islamic educational institutions with a focus on inclusive leadership strategies in managing diversity. The case study was conducted at MTs Negeri 2 Karawang, which has a school community with heterogeneous cultural backgrounds, languages, and levels of religious understanding. The method used was descriptive qualitative with data collection techniques including interviews, observation, and documentation. Data were analyzed using the interactive model of Miles and Huberman. The results show that multicultural management in madrasas is implemented through strengthening inclusive leadership, integrating multicultural values ​​into the curriculum, implementing cooperative learning strategies, facilitating cross-cultural social interaction, and increasing teacher capacity through training. This implementation has resulted in increased social cohesion, student tolerance and inclusiveness, and the quality of learning in madrasas. Furthermore, the study found that this success is supported by the implementation of Islamic values ​​such as brotherhood, justice, and deliberation. However, challenges remain, such as resistance from some teachers and parents and limited understanding of multicultural pedagogy. Therefore, a sustainable strengthening strategy is needed to ensure the comprehensive internalization of multicultural values.